Optimal Allocation of Reactive Power Compensators in Transmission Networks Considering Wind Energy Uncertainty - Khan, Numan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
This thesis addresses the problem of finding the optimal configuration (location and size) of static var compensator (SVC) considering the intermittent nature of wind power in the transmission system. A probabilistic load flow (PLF) integrated with a five-point estimation method is used to model the wind power uncertainties by discretizing wind power distribution into five discrete points. Consolidating PLF with multi-objective non-dominated sorting genetic algorithm (NSGA-II), location and size of SVC can be optimally allocated considering the impacts of wind power uncertainties. This method aims to minimize system operating cost, power loss reduction and voltage profile enhancement. The viability of the applied method is validated on the IEEE 30 bus system. Simulation outcomes demonstrate the viability of the applied method in minimizing different objective functions under the vague nature of wind power. The total voltage profile is improved by 33.2%, while the total power loss of the mentioned power system is reduced by almost 40% after installation of SVCs and wind turbine.

ÖZ: Bu tez, iletim sisteminde rüzgar enerjisinin aralıklı doğası göz önünde bulundurularak Statik Var Kompansatör (SVC) en uygun yapılandırmasını (konum, boyut ve sayı) bulma sorununu ele almaktadır. Olasılıksal yük akışı (PLF) tabanlı beş nokta tahmin yöntemi beş ayrı nokta içine rüzgar gücü dağılımı ayrıştırarak rüzgar gücü belirsizlikleri modellemek için kullanılır. PLF'nin çok nesnel olmayan hakim olmayan genetik algoritma (NSGA-II) ile birleştirilmesi, SVC'nin konumu ve boyutlandırılması, rüzgar enerjisi belirsizliklerinin etkileri göz önünde bulundurularak en iyi şekilde tahsis edilebilir. Bu yöntem, sistem işletme maliyetini, güç kaybını azaltmayı ve voltaj profili iyileştirmeyi en aza indirmeyi amaçlamaktadır. Uygulanan yöntemin uygulanabilirliğini göstermek için IEEE 30 veri yolunda doğrulanır. Simülasyon sonuçları, rüzgar enerjisinin belirsiz doğası altında farklı nesnel fonksiyonlarıen en aza indirmede uygulanan yöntemin etkinliğini kanıtlamaktadır. Bahsedilen güç sisteminin toplam voltaj sapması% 33.2 oranında artarken, güç sisteminin toplam güç kaybı, SVC'lerin ve rüzgar türbininin takılmasından sonra neredeyse% 40 oranında azalır.
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2020. Supervisor: Assoc. Prof. Dr. Reza Sirjani.
Keywords: Electrical and Electronic Engineering; Electric power systems--Wind Energy; Static Var Compensator; Wind Power Uncertainty; 5-Points Estimation Method; NSGA-II